Ore sample preparation and determination methods

The processing of ore samples of different particle sizes through grading screening and appropriate sample preparation methods has solved the problem of uneven sample preparation and improved the accuracy and representativeness of the test results.

CN119321941BActive Publication Date: 2025-03-28CHANGCHUN GOLD RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411875026.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

In the prior art, the ore samples are unevenly prepared, resulting in inaccurate detection results.

Method used

By dividing the powder sample to be tested into samples of different particle sizes and selecting different sample preparation methods according to their particle size distribution, including wet screening, filtration and drying, mixing with liquid glue or thermosetting inlays, etc., the uniformity and representativeness of the sample are ensured.

Benefits of technology

The uniform sample preparation of ore samples is achieved, the accuracy and representativeness of the detection results are improved, and the problems of agglomeration and segregation are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119321941B_ABST
    Figure CN119321941B_ABST
Patent Text Reader

Abstract

The present application provides a method for preparing and measuring ore samples, which belongs to the field of process mineralogy, wherein the method for preparing ore samples includes two wet screenings to divide the samples into samples 11, 31 and 41, mixing sample 11 with liquid glue, heating and shaking to remove bubbles, heating and curing, side cutting, secondary mounting, and re-curing to obtain sample 12; mixing sample 31 with thermosetting mounting material, loading into a mounting machine for heating and pressurizing to cure, and obtaining sample 32; mixing sample 41 with resin particles, adding 3-5 mL of liquid glue at low temperature, stirring and mixing, vacuuming to remove bubbles, curing, adding liquid glue again to a total volume of 10-15 mL to cure, and obtaining sample 42; grinding and polishing and carbon spraying treatment are performed on different samples respectively. The present application selects different sample preparation methods according to the different particle size distributions of samples 11, 31 and 41, so that the sample preparation of samples with different particle size distributions is more uniform and more representative.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of process mineralogy, and in particular to a method for preparing and measuring an ore sample. Background Art

[0002] Process mineralogy research is the foundation of geological and mining research. The determination of mineral composition usually involves first crushing the mineral into powder samples, and then preparing the powder samples for analysis and testing using automatic mineralogical analysis equipment. The sample preparation method is generally to solidify the powder sample in a resin material, and then go through processes such as cutting and grinding, carbon spraying, etc. However, due to the great differences in the properties of minerals, the powder samples after crushing and grinding have uneven particle size, making sample preparation difficult. In addition, the powder samples after sample preparation are unevenly distributed, and separation and segregation are prone to occur, resulting in unrepresentative test results.

[0003] In order to improve the accuracy of analysis, there are two main methods for sample preparation. One is to mix the powder sample with the liquid resin material and stir the mixture to achieve a uniform effect; the other is to add graphite during sample preparation to disperse the sample. The first method cannot solve the problem of fine-grained minerals agglomerating into false particles caused by the agglomeration or adjoining of fine particles, which leads to inaccurate test results. At the same time, due to the differences in specific gravity and morphology of minerals of different particle sizes in the powder sample, the mineral particles with high specific gravity and large particle size settle quickly in the liquid resin and mostly settle in the bottom layer. When only the cross-section of the bottom layer is polished, the distribution of ore particles on the polished surface deviates from the distribution of ore particles during the mineral processing process, further affecting the accuracy of the test results. The second method has a poor dispersion effect due to the large morphological deviation between graphite and a large number of powder samples; and graphite has a light specific gravity, which is difficult to mix evenly during sample preparation, further affecting the dispersion effect, thereby affecting the accuracy of the test. Summary of the invention

[0004] In view of the technical problems existing in the background technology, the present application provides a method for preparing and measuring ore samples, aiming to solve the technical problem of uneven sample preparation in the prior art.

[0005] In a first aspect, an embodiment of the present application provides a method for preparing an ore sample, comprising the following steps:

[0006] S1. Dry and weigh 200-3000g of the powder sample to be tested, with a mass of dg; then add water to the powder sample to be tested and mix well, and perform wet sieving. The sample on the sieve is recorded as sample 1, and the sample under the sieve is recorded as sample 2;

[0007] S2, wet-sieving the sample 2, recording the sample on the sieve as sample 3, and recording the sample under the sieve as sample 4;

[0008] S3, the sample 1 was filtered, dried and weighed, the mass was ag, then mixed and sampled 4~9g, recorded as sample 11; the sample 3 was filtered, dried and weighed, the mass was bg, then mixed and sampled 2~5g, recorded as sample 31; the sample 4 was filtered, dried and weighed, the mass was cg, then mixed and sampled 1~3g, recorded as sample 41;

[0009] S4, mixing the sample 11 and the liquid glue in a preset ratio, heating and shaking to remove bubbles, heating and curing, side cutting, secondary embedding, and curing again to obtain a sample 12;

[0010] S5, mixing the sample 31 and the thermosetting mounting material in a preset ratio, placing the mixture in a mounting machine, heating and pressurizing the mixture for curing, and obtaining a sample 32;

[0011] S6, after mixing the sample 41 and the resin particles in a preset ratio, add 3-5 mL of liquid glue at low temperature, stir and mix, evacuate to remove bubbles, add liquid glue again to a total volume of 10-15 mL after curing, and cure again to obtain sample 42;

[0012] S7. Grind and polish the sample 12, sample 32 and sample 42 and perform carbon spraying treatment to obtain sample 13, sample 33 and sample 43 respectively.

[0013] In the technical solution of the embodiment of the present application, the powder sample to be tested is first divided into sample 1 and sample 2, and the large particles and small particles are initially separated. Then, sample 2 is further screened to further reduce the deviation of the sample particle size in sample 3 and sample 4, so as to facilitate uniform sample preparation. In the specific sample preparation process, different sample preparation methods are selected according to the different particle size distributions of sample 11, sample 31, and sample 41, so that the sample preparation of samples with different particle size distributions is more uniform and more representative. Finally, samples 12, sample 32, and sample 42 with uniform mineral distribution are ground, polished, and carbon-sprayed to provide favorable conditions for subsequent analysis and detection.

[0014] In some embodiments, in step S6, the particle size of the resin particles is 5~10 μm, the volume ratio of the sample 41 to the resin particles is 1:1.5~1:3.5, the liquid glue is a compound of epoxy resin glue and curing agent in a ratio of 1:1~2:1, the low temperature is 10~20°C, the stirring is slow stirring, and the rotation speed is 20~30r / min.

[0015] In this embodiment, based on the relatively small particle size of the sample 41, it is mixed with the resin particles. The particle sizes of the sample 41 and the resin particles are close and the specific gravity is small, which is more conducive to mixing the two and preventing the agglomeration of the sample 41. Then, liquid glue is added at low temperature. The small particle sample 41 and the resin particles are further mixed by adding the liquid substance, and the low temperature process prevents the resin particles from liquefying and causing the disadvantage of uneven sample preparation. In addition, the resin particles do not affect the subsequent analysis and detection process.

[0016] In some embodiments, in step S5, the particle size of the thermosetting embedding material is 10-20 μm, the mass ratio of the sample 31 to the thermosetting embedding material is 1:0.8-1:2.5, and the thermosetting embedding material is a thermosetting phenolic epoxy resin.

[0017] In this embodiment, due to the moderate particle size of sample 31, it is easier to mix with the thermosetting inlay material, thereby making the distribution of minerals in sample 32 more uniform. At the same time, the particle size of sample 31 is moderate, and it will not agglomerate or stratify during the heating and pressurizing curing process, further improving the uniformity of sample 32.

[0018] In some embodiments, in step S4, the liquid glue is a compound of epoxy resin glue and curing agent in a ratio of 1:1 to 2:1, the amount of liquid glue added is 10 to 15 mL, the heating and shaking is ultrasonic shaking at 30 to 50°C for 25 to 35 minutes, the heating and curing temperature is 40 to 65°C, the side cutting is cutting the cured sample from top to bottom in a vertical direction, and the re-curing is adding 10 to 15 mL of liquid glue again and then heating to 30 to 50°C until curing.

[0019] In this embodiment, according to the characteristic of sample 11 that its particle size is relatively large, it is mixed with liquid glue, heated and shaken to remove bubbles, further accelerating the stratification of the sample, allowing large particles to quickly and differentially settle, and then heated and cured. The present application performs side cutting on the cured sample to expose minerals of different particle sizes distributed on the side surface, making the sample on the side surface more representative, and then solidifies again, so that minerals of different particle sizes are evenly distributed on the test surface of sample 12, thereby improving the accuracy of the test of sample 12.

[0020] In some embodiments, in step S1, the drying is performed at 80-95°C for at least 1 hour and then cooled to room temperature; the wet screening uses a sieve of 50-80 mesh.

[0021] In some embodiments, in step S2, the wet screening uses a sieve of 600-1000 mesh.

[0022] In this embodiment, the powder sample to be tested is sieved twice in step S1 and step S2 to be divided into three samples with different particle sizes. On the one hand, the particle size distribution of the minerals in each sample is relatively uniform. On the other hand, different samples are matched with different sample preparation methods to improve the uniformity and representativeness of sample preparation.

[0023] In some embodiments, in step S3, the drying is performed at 80-95° C. for at least 1 hour and then cooled to room temperature.

[0024] In some embodiments, in step S7, the sample 12 is polished with a polishing material of 6 μm or more, the sample 32 is polished with a polishing material of 3 μm or more, and the sample 42 is polished with a polishing material of 1 μm or more, and the polishing is performed until the surface is smooth and free of streaks, and the polishing time does not exceed 5 minutes.

[0025] In this embodiment, the prepared samples are ground and polished using different polishing materials to prevent damage to the samples during the grinding and polishing process.

[0026] In a second aspect, the embodiment of the present application provides a method for measuring an ore sample, wherein the prepared samples 13, 33 and 43 are tested in an automatic mineralogical analysis device to obtain the required parameters N13, N33 and N43, and the obtained parameter data are calculated to obtain the test result M of the powder sample to be tested;

[0027] The calculation formula of M is: M=(N13×a+N33×b+N43×c) / d;

[0028] Wherein, a is the mass of sample 1 after drying; b is the mass of sample 3 after drying; c is the mass of sample 4 after drying; d is the mass of the powder sample to be tested after drying.

[0029] In the technical solution of the embodiment of the present application, different samples are tested separately on the basis of uniform sample preparation, and the test parameter results of the powder sample to be tested are calculated according to the content of different samples, and the accuracy of the measurement results is higher.

[0030] In some embodiments, during the test process, the magnification of the sample 13 is 100 to 300 times, and the number of tested particles is 30,000 to 50,000 particles; the magnification of the sample 33 is 250 to 500 times, and the number of tested particles is 20,000 to 40,000 particles; the magnification of the sample 43 is 600 to 1,200 times, and the number of tested particles is 10,000 to 30,000 particles.

[0031] In this embodiment, different samples are magnified to different multiples according to the different mineral particle sizes in sample 13, sample 33 and sample 43 to facilitate analysis and detection; at the same time, the number of test particles in sample 13, sample 33 and sample 43 is large, which further improves the accuracy and representativeness of the detection.

[0032] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0034] Figure 1 This is a flow chart of the method for preparing ore samples in the embodiments of the present application;

[0035] Figure 2 This is the result of the automatic mineralogical analysis of sample 13 in Example 1 of the present application, with a scale of 5 mm;

[0036] Figure 3 This is the result of the automatic mineralogical analysis of sample 33 in Example 1 of the present application, with a scale of 600 μm;

[0037] Figure 4 This is the result of the automatic mineralogical analysis of sample 43 in Example 1 of the present application, with a scale of 20 μm;

[0038] Figure 5 This is the result of the automatic mineralogical analysis of sample 43 in comparative example 1 of the present application, with a scale of 10 μm;

[0039] Figure 6 This is the result of automatic mineralogical analysis of the sample in Comparative Example 7 of the present application, with a scale of 1 mm. DETAILED DESCRIPTION

[0040] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0042] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0043] The commonly used sample preparation method of mixing powder samples with liquid resin materials and stirring the resulting mixture cannot effectively solve the problem of fine-grained minerals agglomerating into false particles caused by agglomeration or adjoining of fine particles, thus leading to inaccurate test results. At the same time, the method of doping with graphite during sample preparation has a poor dispersion effect due to the large morphological deviation between graphite and a large number of powder samples; and graphite has a light specific gravity and is difficult to mix evenly during sample preparation, further affecting the dispersion effect and thus the accuracy of the test.

[0044] In order to solve the technical problem of uneven sample preparation, the present application provides a method for sample preparation and determination of ore samples, wherein the powder sample to be tested is first divided into sample 1 and sample 2, and large particles and small particles are preliminarily separated, and then sample 2 is further screened to further reduce the deviation of sample particle size in sample 3 and sample 4, so as to facilitate uniform sample preparation. In the specific sample preparation process, different sample preparation and inlaying methods are selected according to the different particle size distributions of sample 11, sample 31, and sample 41, which solves the problems of agglomeration and sedimentation segregation of fine-grained samples, making the sample preparation of samples with different particle size distributions more uniform and more representative. Finally, samples 12, sample 32, and sample 42 with uniform mineral distribution are ground, polished, and carbon-sprayed to provide favorable conditions for subsequent analysis and detection. In addition, the present method has large sampling volume, simple sample preparation, wide applicability to samples, good test effect, and provides reliable and stable samples for process mineralogy testing and analysis.

[0045] In a first aspect, an embodiment of the present application provides a method for preparing an ore sample, comprising the following steps:

[0046] S1. Dry and weigh 200-3000g of the powder sample to be tested, with a mass of dg; then add water to the powder sample to mix well, and perform wet sieving. The sample on the sieve is recorded as sample 1, and the sample under the sieve is recorded as sample 2. The sampling amount of the powder sample to be tested is adjusted according to the particle size. The sampling amount of finer particles is less, and the sampling amount of coarse particles is appropriately increased.

[0047] First, dry and weigh the powder sample to be tested to obtain the precise mass of the powder sample to be tested, which guarantees the accuracy of the subsequent measurement results. Then add an appropriate amount of water to facilitate the subsequent wet screening without affecting the screening process due to excessive or insufficient water. The powder sample to be tested is divided into sample 1 and sample 2 after screening, and the large particles and small particles are initially separated, which is convenient for the subsequent sample preparation of samples of different particle sizes using different methods to prevent the problem of uneven sample preparation caused by particle size deviation.

[0048] S2. Wet-screen sample 2. The sample on the sieve is recorded as sample 3, and the sample under the sieve is recorded as sample 4.

[0049] Then, sample 2 is further screened to further reduce the deviation of sample particle size in samples 3 and 4 to facilitate uniform sample preparation.

[0050] S3. Filter, dry and weigh sample 1, with a mass of ag. Then mix and sample 4 to 9 g, which is recorded as sample 11. Filter, dry and weigh sample 3, with a mass of bg. Then mix and sample 2 to 5 g, which is recorded as sample 31. Filter, dry and weigh sample 4, with a mass of cg. Then mix and sample 1 to 3 g, which is recorded as sample 41.

[0051] Samples of different particle size ranges are dried and mixed to make the samples of different particle size ranges uniform in composition, thereby making the samples taken representative. At the same time, samples of different masses are taken according to the characteristics of samples of different particle size ranges to facilitate subsequent sample preparation.

[0052] S4, after the sample 11 and the liquid glue are mixed in a preset ratio, the sample 11 is heated and shaken to remove bubbles, heated and cured, side cut, secondary inlayed, and cured again to obtain the sample 12. No bubble removal is required for the secondary curing.

[0053] According to the characteristics of sample 11 with relatively large particle size, it is mixed with liquid glue, heated and shaken to remove bubbles, further accelerating the differentiated stratification sedimentation of the sample, allowing large particles to settle quickly, and then heated and cured. The present application performs side cutting on the cured sample, and the minerals of different particle sizes distributed on the side surface are relatively more uniform, and then it is cured again, so that the minerals of different particle sizes in the test surface of sample 12 are evenly distributed, thereby improving the accuracy of the test of sample 12.

[0054] S5. Mix the sample 31 and the thermosetting mounting material in a preset ratio, put them into a mounting machine, heat and pressurize them for curing, and obtain the sample 32.

[0055] According to the characteristics of moderate particle size of sample 31, it is easier to mix with the thermosetting inlay material, thereby making the distribution of minerals in sample 32 more uniform. At the same time, the particle size of sample 31 is moderate, and it will not agglomerate or stratify during the heating and pressurizing curing process, further improving the uniformity of sample 32.

[0056] S6. After mixing sample 41 and resin particles in a preset ratio, add 3-5 mL of liquid glue at low temperature, stir and mix, evacuate to remove bubbles, add liquid glue again to a total volume of 10-15 mL after solidification, solidify again, and obtain sample 42.

[0057] According to the relatively small particle size of sample 41, it is mixed with resin particles. The particle sizes of sample 41 and resin particles are close and the specific gravity is small, which is more conducive to mixing the two and preventing the agglomeration of sample 41. Then, liquid glue is added at low temperature. The small particle sample 41 and resin particles are further mixed by adding liquid substances, and the low temperature process prevents the liquefaction of resin particles from causing uneven sample preparation. In addition, the resin particles do not affect the subsequent analysis and detection process.

[0058] S7. Grind and polish and carbon spray the samples 12, 32 and 42 respectively to obtain the samples 13, 33 and 43.

[0059] Samples 12, 32 and 42 with uniform mineral distribution were polished and carbon sprayed to provide favorable conditions for subsequent analysis and testing.

[0060] Furthermore, in some embodiments, in step S6, the particle size of the resin particles is 5~10μm, the volume ratio of sample 41 to the resin particles is 1:1.5~1:3.5, the liquid glue is a compound of epoxy resin glue and curing agent in a ratio of 1:1~2:1, the low temperature is 10~20℃, the stirring is slow stirring, and the rotation speed is 20~30r / min.

[0061] In the technical solution of the embodiment of the present application, the particle size of the resin particles is controlled to be 5-10 μm, which is close to the particle size of sample 41. At the same time, the volume ratio of sample 41 to resin particles is controlled to be 1:1.5-1:3.5, and the sample 41 is slowly stirred and mixed with liquid glue at low temperature, so that the two are mixed evenly while ensuring that the content of sample 41 in the mixture formed by the two is as high as possible, so that in the subsequent test process, the content of sample 41 distributed on the test surface is relatively high, the number of particles measured is large, the detection accuracy is higher, and it is more representative. At the same time, slow stirring prevents the stratification of sample 41. Then, it is mixed with liquid glue again at low temperature to increase the volume of the sample without affecting the distribution of minerals in sample 41, which is convenient for subsequent analysis and detection.

[0062] Furthermore, in some embodiments, in step S5, the particle size of the thermosetting embedding material is 10-20 μm, the mass ratio of the sample 31 to the thermosetting embedding material is 1:0.8-1:2.5, and the thermosetting embedding material is a thermosetting phenolic epoxy resin.

[0063] In the technical solution of the embodiment of the present application, the particle size of the thermosetting embedding material is controlled to be 10~20μm, which is close to the particle size of sample 31. At the same time, the mass ratio of sample 31 to the thermosetting embedding material is controlled to be 1:0.8~1:2.5, so that the two are mixed evenly while ensuring that the content of sample 31 in the mixture formed by the two is as high as possible, so that in the subsequent testing process, the content of sample 31 distributed on the test surface is relatively large, the number of measured particles is large, the detection accuracy is higher, and it is more representative.

[0064] Furthermore, in some embodiments, in step S4, the liquid glue is prepared by compounding epoxy resin glue and curing agent in a ratio of 1:1 to 2:1, the amount of liquid glue added is 10 to 15 mL, the heating and shaking is ultrasonic shaking at 30 to 50°C for 25 to 35 min, the heating and curing temperature is 40 to 65°C, the side cutting is cutting the cured sample from top to bottom along the vertical direction, and the re-curing is placing the cut surface at the bottom (i.e., rotating the cut surface 90°) and adding 10 to 15 mL of liquid glue again and then heating to 30 to 50°C until it is cured.

[0065] Furthermore, in some embodiments, in step S1, drying is performed at 80-95°C for at least 1 hour and then cooled to room temperature; a sieve of 50-80 mesh is used for wet sieving. If the particle size of the powder sample to be tested is coarse, a sieve with a coarse aperture can be added to continue sieving.

[0066] Furthermore, in some embodiments, in step S2, a sieve of 600-1000 mesh is used for wet screening.

[0067] In the technical solution of the embodiment of the present application, the powder sample to be tested is sieved twice in step S1 and step S2 to be divided into three samples with different particle sizes. On the one hand, the particle size distribution of the minerals in each sample is relatively uniform. On the other hand, different samples are matched with different sample preparation methods to improve the uniformity and representativeness of sample preparation.

[0068] Furthermore, in some embodiments, in step S3, the drying is performed at 80-95° C. for at least 1 hour and then cooled to room temperature.

[0069] Further, in some embodiments, in step S7, sample 12 is polished with a polishing material of 6 μm or more, sample 32 is polished with a polishing material of 3 μm or more, and sample 42 is polished with a polishing material of 1 μm or more, and the polishing is performed until it is smooth and streak-free, and the polishing time does not exceed 5 minutes.

[0070] In the technical solution of the embodiment of the present application, the prepared samples are ground and polished using different polishing materials to prevent damage to the samples during the grinding and polishing process.

[0071] In a second aspect, the embodiment of the present application provides a method for measuring the samples prepared above, wherein sample 13, sample 33 and sample 43 are tested in an automatic mineralogical analysis device respectively to obtain the required parameters N13, N33 and N43, and the obtained parameter data are calculated to obtain the test result M of the powder sample to be tested;

[0072] The calculation formula of M is: M=(N13×a+N33×b+N43×c) / d;

[0073] Wherein, a is the mass of sample 1 after drying; b is the mass of sample 3 after drying; c is the mass of sample 4 after drying; d is the mass of the powder sample to be tested after drying.

[0074] On the basis of uniform sample preparation, different samples are tested separately, and the test parameter results of the powder sample to be tested are calculated according to the content of different samples, so that the accuracy of the test results is higher.

[0075] Furthermore, in some embodiments, during the test process, the magnification of sample 13 is 100~300 times, and the number of tested particles is 30,000~50,000 particles; the magnification of sample 33 is 250~500 times, and the number of tested particles is 20,000~40,000 particles; the magnification of sample 43 is 600~1200 times, and the number of tested particles is 10,000~30,000 particles.

[0076] In the technical solution of the embodiment of the present application, different samples are magnified by different multiples according to the different mineral particle sizes in sample 13, sample 33 and sample 43 to facilitate analysis and detection; at the same time, the number of test particles in sample 13, sample 33 and sample 43 is relatively large, which further improves the accuracy and representativeness of the detection.

[0077] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.

[0078] Example 1

[0079] A method for preparing an ore sample is described by taking gold ore (the metal sulfide is mainly pyrite, and the content of other metal sulfides is very low and can be ignored) as an example, comprising the following steps:

[0080] S1. Dry 512 g of the pre-ground powder sample at 80 °C for at least 1 h, cool it to room temperature and weigh it. The mass is d = 500 g. Then add water to the powder sample and mix it evenly. Use a sieve with 80 mesh for wet sieving. The sample on the sieve is recorded as sample 1, and the sample under the sieve is recorded as sample 2.

[0081] S2. Use a sieve of 800 mesh to wet-screen sample 2. The sample on the sieve is recorded as sample 3, and the sample under the sieve is recorded as sample 4.

[0082] S3. Filter sample 1, dry it at 80°C for at least 1h, then cool it to room temperature and weigh it. The mass is a = 36g. Then mix and sample 5g, which is recorded as sample 11. Filter sample 3, dry it at 80°C for at least 1h, then cool it to room temperature and weigh it. The mass is b = 422g. Then mix and sample 3g, which is recorded as sample 31. Filter sample 4, dry it at 80°C for at least 1h, then cool it to room temperature and weigh it. The mass is c = 42g. Then mix and sample 2g, which is recorded as sample 41.

[0083] S4, after mixing sample 11 and liquid glue in a preset ratio, heating and shaking to remove bubbles, heating and curing, side cutting, secondary embedding, and re-curing to obtain sample 12. Among them, the liquid glue is a compound of epoxy resin glue and curing agent in a ratio of 2:1, the amount of liquid glue added is 12mL, heating and shaking is ultrasonic shaking at 50℃ for 30min, the temperature of heating and curing is 60℃, side cutting is cutting the cured sample from top to bottom in the vertical direction, and re-curing is placing the cut surface below, adding 12mL of liquid glue again, and then heating to 60℃ until curing.

[0084] S5. Mix the sample 31 and the thermosetting inlay material in a preset ratio, and then put them into an inlay machine for heating and pressurizing to cure, thereby obtaining the sample 32. The particle size of the thermosetting inlay material is 10 μm, the mass ratio of the sample 31 to the thermosetting inlay material is 1:2, the thermosetting inlay material is a thermosetting phenolic epoxy resin, the heating and pressurizing temperature is 130°C, and the pressure is 250 Bar.

[0085] S6. After mixing sample 41 and resin particles in a preset ratio, add 3 mL of liquid glue at low temperature, stir and mix, vacuum to remove bubbles, and solidify at room temperature, then add liquid glue again to a total volume of 10 mL, solidify at room temperature again, and obtain sample 42. The particle size of the resin particles is 5 μm, the volume ratio of sample 41 to the resin particles is 1:2, the liquid glue is a compound of epoxy resin glue and curing agent in a ratio of 2:1, the low temperature is 10°C, the stirring is slow stirring, and the speed is 25 r / min.

[0086] S7. Grind and polish the sample 12, sample 32 and sample 42 and perform carbon spraying treatment respectively to obtain sample 13, sample 33 and sample 43. Sample 12 is polished with a 6 μm polishing material, sample 32 is polished with a 3 μm polishing material, and sample 42 is polished with a 1 μm polishing material until it is smooth and free of streaks, and the polishing time is 3 min.

[0087] Example 2

[0088] A method for determining the pyrite content in the sample prepared in Example 1, wherein sample 13, sample 33 and sample 43 are tested in an automatic mineralogical analysis device, respectively, and the pyrite contents in sample 13, sample 33 and sample 43 are obtained as N13=6.28%, N33=10.55% and N43=3.71%. During the testing process, the magnification of sample 13 is 200 times, and the number of test particles is 40,000; the magnification of sample 33 is 300 times, and the number of test particles is 30,000; the magnification of sample 43 is 800 times, and the number of test particles is 20,000. The mineralogical analysis device used is an MLA650 mineral parameter automatic analysis system.

[0089] The obtained parameter data is calculated to obtain the pyrite content M of the powder sample to be tested:

[0090] M = (N13×a+N33×b+N43×c) / d

[0091] = (6.28%×36+10.55%×422+3.71%×42) / 500

[0092] = 9.668%.

[0093] At the same time, if Figure 2 As shown, this is the result of the automatic mineralogy analysis of sample 13 during the detection process of the automatic mineralogy analysis equipment. Figure 2 It can be seen that the mineral particles in sample 13 are evenly distributed and well dispersed, and can be clearly distinguished during testing, indicating that the way sample 11 is processed can improve the accuracy of detection.

[0094] like Figure 3 As shown, this is the result of the automatic mineralogical analysis of sample 33 during the detection process of the automatic mineralogical analysis equipment. Figure 3 It can be seen that the minerals in sample 33 are evenly distributed without adhesion or agglomeration, which shows that the processing method of sample 31 can improve the accuracy of detection.

[0095] like Figure 4 As shown, this is the result of the automatic mineralogical analysis of sample 43 during the detection process of the automatic mineralogical analysis equipment. Figure 4It can be seen that the mineral particles in sample 43 are fine and the particle size is relatively uniform. After sample preparation by this method, there is no agglomeration between the particles in sample 43, and the sample preparation effect is good, which shows that the way of processing sample 41 can improve the accuracy of detection.

[0096] In order to further illustrate the accuracy of the analysis results of the present method, chemical analysis was performed on samples 11, 31 and 41 respectively (chemical analysis was performed to detect the sulfur content in pyrite, and then the sulfur content was converted into the content of pyrite). After the measurement, the sulfur content in sample 11 was 3.36%, and the pyrite content after conversion was 6.29%, which was basically consistent with the N13=6.28% tested in the automatic mineralogical analysis equipment; the sulfur content in sample 31 was 5.65%, and the pyrite content after conversion was 10.57%, which was basically consistent with the N33=10.55% tested in the automatic mineralogical analysis equipment; the sulfur content in sample 41 was 1.98%, and the pyrite content after conversion was 3.70%, which was basically consistent with the N43=3.71% tested in the automatic mineralogical analysis equipment; it can be seen that after the processing method of the present application for samples of different particle sizes is prepared, the detection accuracy is basically consistent with the chemical analysis detection results, and the detection accuracy is high. At the same time, without screening, the ground powder to be tested is directly sampled and chemically analyzed (in order to make the sampling representative, the initial sampling volume is relatively large, and then sampling is performed through multiple reductions). The sulfur content in the sample is 5.17%, and the pyrite content after conversion is 9.67%, which is consistent with the M=9.668% calculated by this application, further indicating that the accuracy of the detection of this application is high. Among them, the conversion formula for sulfur content and pyrite content is: pyrite content = sulfur content × 119.975 / 64.13 = sulfur content / 53.45%.

[0097] That is, by comparing the values ​​obtained from chemical analysis with the data obtained from the automatic mineralogical analysis equipment, it is found that the test results of the samples prepared by the sample preparation method of the present application have a high degree of match with the chemical analysis results and the data is accurate.

[0098] Chemical analysis of sulfur content in pyrite is carried out by differential method or acetic acid-hydrogen peroxide leaching method. The differential method is to subtract the sulfur content in natural sulfur and sulfate from the total sulfur content. For the detection of total sulfur content, please refer to GB / T7739.8-2007 on the detection of sulfur content, and for the detection of sulfur in natural sulfur and sulfate, please refer to the article "Application of Sulfur Phase Analysis and Determination Method" published by Zhang Qi of Changchun Gold Research Institute. For the acetic acid-hydrogen peroxide leaching method, please refer to the article "Application of Sulfur Phase Analysis and Determination Method" published by Zhang Qi of Changchun Gold Research Institute.

[0099] Comparative Example 1

[0100] A method for determining the pyrite content in an ore sample. The sample preparation method of the ore sample in this comparative example is compared with that in Example 1, except that in step S6, the temperature for adding the liquid glue is 30°C, and the rest is substantially the same as in Example 1 and will not be repeated here. The pyrite content is determined by the same automatic mineralogical analysis method as in Example 2, with N13=6.28%, N33=10.55%, N43=15.75%, and M=10.679%.

[0101] like Figure 5 As shown, this is the result of the automatic mineralogical analysis of sample 43 during the detection process of the automatic mineralogical analysis equipment. Figure 5 The black particles are particles that cannot be identified during the detection process due to particle agglomeration. It can be seen that the treatment of sample 41 in comparative example 1 easily causes agglomeration of small particles.

[0102] Comparative Example 2

[0103] A method for determining the pyrite content in an ore sample. The sample preparation method of the ore sample in this comparative example is compared with that in Example 1, except that in step S6, the resin particles are replaced with calcium carbonate of the same particle size. The rest is substantially the same as in Example 1 and will not be repeated here. The pyrite content is determined by the same method as in Example 2, with N13=6.28%, N33=10.55%, N43=20.14%, and M=11.048%.

[0104] Comparative Example 3

[0105] A method for determining the pyrite content in an ore sample. The sample preparation method of the ore sample in this comparative example is compared with that in Example 1, except that, in step S6, the resin particles are replaced with high-purity quartz of the same particle size (quartz content is 99.90% and above), and the rest is substantially the same as in Example 1 and will not be repeated here. The pyrite content is determined by the same method as in Example 2, with N13=6.28%, N33=10.55%, N43=20.03%, and M=11.039%.

[0106] The pyrite content N43 of sample 43 in comparative examples 1-3 is 15.75%, 20.14% and 20.03% respectively, which is significantly different from the 3.71% obtained by chemical analysis and the N43=3.71% obtained by testing in the automatic mineralogical analysis equipment in Example 2. This indicates that the treatment method of sample 41 in comparative examples 1-3 makes the test result of pyrite in sample 43 obviously higher, which in turn leads to a higher content of pyrite in the entire powder sample to be tested and an inaccurate result.

[0107] Comparative Example 4

[0108] A method for determining the pyrite content in an ore sample. The sample preparation method of the ore sample in this comparative example is compared with that in Example 1, except that the treatment of sample 31 in step S5 and the treatment of sample 41 in step S6 are the same as the treatment of sample 11 in step S4, the ratios of sample 31, sample 41 and liquid glue are equal to the ratio of sample 11 and liquid glue, and the rest are substantially the same as in Example 1 and will not be repeated here. The pyrite content is determined by the same method as in Example 2, with N13=6.28%, N33=8.61%, N43=1.02%, and M=7.805%.

[0109] Compared with the results obtained by chemical analysis and the results obtained by testing in the automatic mineralogical analysis equipment in Example 2, the pyrite content of samples 33 and 43 in Comparative Example 4 is low, and the pyrite content in the entire powder sample to be tested is low.

[0110] Comparative Example 5

[0111] A method for determining the pyrite content in an ore sample. The sample preparation method of the ore sample in this comparative example is compared with that in Example 1, except that the treatment of sample 11 in step S4 and the treatment of sample 41 in step S6 are the same as the treatment of sample 31 in step S5, the ratios of sample 11, sample 41 and thermosetting mounting materials are equal to the ratio of sample 31 and thermosetting mounting materials, and the rest are substantially the same as in Example 1 and will not be repeated here. The pyrite content is determined by the same method as in Example 2, with N13=2.51%, N33=10.55%, N43=1.45%, and M=9.207%.

[0112] Compared with the results obtained by chemical analysis and the results obtained by testing in automatic mineralogical analysis equipment in Example 2, the pyrite content of samples 13 and 43 in Comparative Example 5 is low, and the pyrite content in the entire powder sample to be tested is low.

[0113] Comparative Example 6

[0114] A method for determining the pyrite content in an ore sample. The sample preparation method of the ore sample in this comparative example is compared with that in Example 1, except that the treatment of sample 11 in step S4 and the treatment of sample 31 in step S5 are the same as the treatment of sample 41 in step S6, the ratios of sample 11, sample 31 and resin particles and liquid glue are equal to the ratios of sample 41 and resin particles and liquid glue, and the rest are substantially the same as in Example 1 and will not be repeated here. The pyrite content is determined by the same method as in Example 2, with N13=11.52%, N33=26.74%, N43=3.71%, and M=23.710%.

[0115] Compared with the results obtained by chemical analysis and the results obtained by testing in automatic mineralogical analysis equipment in Example 2, the pyrite content of samples 13 and 33 in Comparative Example 6 was higher, and the pyrite content in the entire powder sample to be tested was significantly higher.

[0116] From the results of Comparative Examples 4-6, it can be seen that treating samples of different particle sizes with the same method will lead to deviations in the test results. It can be seen that only by treating minerals of different particle sizes in a specific way can the accuracy of the test be improved.

[0117] Comparative Example 7

[0118] A method for determining the content of pyrite in an ore sample. The sample preparation method of the ore sample in the comparative example is specifically as follows:

[0119] S1. Dry 512 g of the pre-ground powder sample at 80 °C for at least 1 h, cool it to room temperature and weigh it. The mass is d = 500 g.

[0120] S2. Take 5 g of sample and prepare it according to the treatment method of sample 11 in Example 1. The ratio of the 5 g sample to the liquid glue is equal to the ratio of the sample 11 to the liquid glue. After sample preparation, the pyrite content is determined in an automatic mineralogical analysis equipment, M=7.42%, which is obviously low.

[0121] At the same time, if Figure 6 As shown in the figure, it is the result of the automatic mineralogy analysis of the sample during the detection process of the automatic mineralogy analysis equipment. Figure 6 It can be seen that without screening treatment, the sample particles have a large deviation and agglomeration.

[0122] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing an ore sample, characterized in that: The steps include: S1. Dry and weigh 200-3000g of the powder sample to be tested, with a mass of dg; then add water to the powder sample to be tested and mix well, and perform wet sieving. The sample on the sieve is recorded as sample 1, and the sample under the sieve is recorded as sample 2; S2, wet-sieving the sample 2, recording the sample on the sieve as sample 3, and recording the sample under the sieve as sample 4; S3, the sample 1 was filtered, dried and weighed, the mass was ag, then mixed and sampled 4~9g, recorded as sample 11; the sample 3 was filtered, dried and weighed, the mass was bg, then mixed and sampled 2~5g, recorded as sample 31; the sample 4 was filtered, dried and weighed, the mass was cg, then mixed and sampled 1~3g, recorded as sample 41; S4, mixing the sample 11 and the liquid glue in a preset ratio, heating and shaking to remove bubbles, heating and curing, side cutting, secondary embedding, and curing again to obtain a sample 12; S5, mixing the sample 31 and the thermosetting mounting material in a preset ratio, placing the mixture in a mounting machine, heating and pressurizing the mixture for curing, and obtaining a sample 32; S6, after mixing the sample 41 and the resin particles in a preset ratio, add 3-5 mL of liquid glue at low temperature, stir and mix, evacuate to remove bubbles, add liquid glue again to a total volume of 10-15 mL after curing, and cure again to obtain sample 42; S7. Grind and polish the sample 12, sample 32 and sample 42 and perform carbon spraying treatment to obtain sample 13, sample 33 and sample 43 respectively.

2. The method for preparing an ore sample according to claim 1, characterized in that: In step S6, the particle size of the resin particles is 5~10μm, the volume ratio of the sample 41 to the resin particles is 1:1.5~1:3.5, the liquid glue is a compound of epoxy resin glue and curing agent in a ratio of 1:1~2:1, the low temperature is 10~20℃, the stirring is slow stirring, and the rotation speed is 20~30r / min.

3. The method for preparing an ore sample according to claim 1, characterized in that: In step S5, the particle size of the thermosetting embedding material is 10-20 μm, the mass ratio of the sample 31 to the thermosetting embedding material is 1:0.8-1:2.5, and the thermosetting embedding material is a thermosetting phenolic epoxy resin.

4. The method for preparing an ore sample according to claim 1, characterized in that: In step S4, the liquid glue is prepared by compounding epoxy resin glue and curing agent in a ratio of 1:1 to 2:1, the amount of the liquid glue added is 10 to 15 mL, the heating and shaking is ultrasonic shaking at 30 to 50°C for 25 to 35 minutes, the heating and curing temperature is 40 to 65°C, the side cutting is cutting the cured sample from top to bottom in the vertical direction, and the re-curing is adding 10 to 15 mL of liquid glue again and then heating to 30 to 50°C until curing.

5. The method for preparing an ore sample according to claim 1, characterized in that: In step S1, the drying is performed at 80-95° C. for at least 1 hour and then cooled to room temperature; the wet screening is performed using a sieve of 50-80 mesh.

6. The method for preparing an ore sample according to claim 1, characterized in that: In step S2, the wet screening uses a sieve of 600-1000 mesh.

7. The method for preparing an ore sample according to claim 1, characterized in that: In step S3, the drying is performed at 80-95° C. for at least 1 hour and then cooled to room temperature.

8. The method for preparing an ore sample according to claim 1, characterized in that: In step S7, the sample 12 is polished with a polishing material of 6 μm or more, the sample 32 is polished with a polishing material of 3 μm or more, and the sample 42 is polished with a polishing material of 1 μm or more, and the polishing is performed until it is smooth and free of streaks, and the polishing time does not exceed 5 minutes.

9. A method for measuring ore samples, characterized in that: The sample 13, sample 33 and sample 43 prepared according to any one of claims 1 to 8 are tested in an automatic mineralogical analysis device to obtain the required parameters N13, N33 and N43, and the obtained parameter data are calculated to obtain the test result M of the powder sample to be tested; The calculation formula of M is: M=(N13×a+N33×b+N43×c) / d; Wherein, a is the mass of sample 1 after drying; b is the mass of sample 3 after drying; c is the mass of sample 4 after drying; d is the mass of the powder sample to be tested after drying.

10. The method for measuring ore samples according to claim 9, characterized in that: During the test, the magnification of sample 13 was 100-300 times, and the number of tested particles was 30,000-50,000 particles; the magnification of sample 33 was 250-500 times, and the number of tested particles was 20,000-40,000 particles; the magnification of sample 43 was 600-1,200 times, and the number of tested particles was 10,000-30,000 particles.

Citation Information

Patent Citations

  • Optimizing method for preparation of polished session from powder

    CN107271229A

  • Sample preparation method for microcell analysis of occurrence state of elements in wet smelting slag

    CN117929431A